Acute cholecystitis as the first manifestation of primary pure squamous cell carcinoma of the gallbladder; a case report - M. Bahadoram; M. Barahman; M. Davoodi; S. Hassanzadeh (Сибирский онкологический журнал)
Background. SCC of the gallbladder is characterized by more rapid and invasive growth with infiltration of the adjacent organs and less spread to the lymph nodes compared to adenocarcinoma of the gallbladder. It is a rare neoplasm that accounts for 1.4–12.7 % of gallbladder tumors. SCC of the gallbladder has a poor prognosis. symptoms usually appear later when the disease has progressed and the malignancy has reached advanced stages. therefore, usually, the patients expire soon following the diagnosis. the etiology of the SCC of the gallbladder is complex and is mostly associated with gallstones. Case description. We report a case of a 56-year-old man that had been suffering from colicky abdominal pain in the right upper quadrant for about two weeks before his admission. He did not have nausea, vomiting, shortness of breath, fever, lack of appetite, or weight loss. after evaluation, a diagnosis of acute cholecystitis was established and antibiotic therapy was initiated. However, he did not respond to medical therapy and underwent surgery. A tumor mass was detected during surgery. therefore, cholecystectomy and extended right hepatectomy were performed. The pathological evaluation of the biopsy specimen revealed squamous cell carcinoma. consequently, he underwent radiotherapy and chemotherapy and was followed up for two years. He acquired complete tumor remission. Conclusion. The present case highlights the requirement of considering further investigation on the histogenesis of SCC of the gallbladder.